Modified Aluminium Tube Profile to Enhance the Performance of Impact Energy Absorption - Witono Hardi; Tri Suyono; Rudi Hartono (Universitas Khairun, 2022)
The use of thin-walled structures as impact energy absorbers are well known. The thin aluminum cylinder tube is a good impact energy absorber. However, the energy-absorbing design must also have sufficient toughness. In this research, we made modifications to improve the performance of the thin aluminum tube. The thin aluminum cylinder's modification is prepared by adding four grooves along the wall in the axial direction. Numerical modeling was carried out using the finite element method. The impact test is carried out by applying a high speed of 50 m/s to a hammer that hits the axial direction's specimen. Explicit dynamic analysis is used in this modeling. The reaction force is obtained by measuring fixed support at the end of the tube. The total energy as a function of time is received in this simulation. The explicit dynamic simulation results show that the toughness of the modified specimens increased compared to the original model. The amount of energy per unit time at the start of the collision appears to be higher. Likewise, the total deformation in the modified specimen is shorter than in the original specimen. Thus, until the collision's end, the modified thin aluminum tube specimen provides better performance and absorption of impact energy.